Kebiasaan Penggunaan Gadget Dini dengan Perkembangan Psikososial pada Anak Usia Sekolah - Samsul, Wawan Adi Saputra; Sunarti; Asfar, Akbar (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
The development of the times as it is today, especially in the field of technology knowledge and information has progressed very rapidly. One of the fastest growing technologies today is gadgets. The use of gadgets in school-age children has positive and negative impacts, one of the negative impacts of using these gadgets is the inhibition of psychosocial development in school-age children. This study aims to determine the relationship between the use of early gadgets to the psychosocial development of school age children in SDN Goto, Tidore Islands City. The research method used in this research is descriptive correlation using a cross sectional approach. The sampling technique was stratified random sampling with a sample size of 65 respondents. The relationship test used the chi square statistical test with a significance level of Î± = 0.05. The results showed students who used gadgets in the non-routine category were 8 (12.3%), the Routine category was 57 (87.7%) and the psychosocial development of the children in the poor category was 21 (32.3%) and the number of students in the good category was 44 (67.7%). The results showed that there was no relationship between the use of gadgets and the psychosocial development of school-age children at SDN Goto, Tidore Islands City, p = 0.226, greater than Î± = 0.05, this is due to several factors including children still social, learning and playing with friends. -friends as usual even though they use gadgets. The conclusions in this study indicate that there is no relationship between the use of early gadgets on the psychosocial development of school-age children at SDN Goto, Tidore Islands City, and the suggestions of this study hopefully can become information material for parents and teachers to better supervise children in using gadgets.